SAYYID USMAN DAN PANDANGAN KONTROVERSIALNYA TENTANG PEMERINTAH KOLONIAL BELANDA - Idan Dandi (IAIN Syekh Nurjati Cirebon, 2017)
AbstractThe text is about the figure of Sayyid Usman who be a Betawi mufti and lived in the Dutch East Indies colonial times. The figure is a very influential person in his day, because his works can be printed in a very large amount with lithographic printing machine technology that he pioneered in Nusantara. Due to its very brilliant prestige, the colonial officials in Batavia also glanced at it. Not how long, Sayyid Usman was lined up to partner Christian Snouck Hurgronje as a colonial advisor. This study uses a sociological and an intellectual biographical approach. The use of the sociological approach aims to unveil all the motivations and purposes of Sayyid Usman's highly controversial ideas as opposed to the plurality of ideas that are present in that era. While the intellectual biographical approach has the purpose to reveal the various realities of life of the subject being studied, along with the influence it receives so that it becomes the thinking model in his mind. From the description, it is known that what was taught by Shaykh Al Misri (his grandfather) as a child is very influential on the development of Sayyid Usman's thought, including in view of colonial rule. His controversial ideas include supporting the status quo of the occupation of whites (Dutch East Indies) in the Indonesia.Keywords: mufti, ulama, colonial advisor, thought, controversial